2019
DOI: 10.1007/s00167-019-05607-y
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent surgical instrument contamination begins earlier in the uncovered table than in the covered table

Abstract: Purpose Time‐dependent surgical instrument contamination and the effect of covering during arthroplasty have not been investigated. This study aimed to evaluate time‐dependent contamination of surgical instruments and the effect of covering on contamination as well as to perform bacterial typing of contaminated samples. The hypothesis was that covering the surgical instruments would decrease contamination rates. Methods Sixty patients who underwent total knee arthroplasty were randomized and divided into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…While, in real surgery conditions, Uzun et al [ 25 ] showed bacterial growth on PSBTs started after 30 and 60 min in the uncovered sets (6 of 30 [20%]) and covered groups (2 of 30 [6.7%]), respectively ( P = 0.024). Dalstrom et al [ 16 ] found that no contamination has occur in the covered group while, rate of 30% contamination appeared in group without cover after 4 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, in real surgery conditions, Uzun et al [ 25 ] showed bacterial growth on PSBTs started after 30 and 60 min in the uncovered sets (6 of 30 [20%]) and covered groups (2 of 30 [6.7%]), respectively ( P = 0.024). Dalstrom et al [ 16 ] found that no contamination has occur in the covered group while, rate of 30% contamination appeared in group without cover after 4 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Uzun et al [ 25 ] demonstrated the contamination of uncovered and covered PSBTs increases with over time (uncovered group; contamination rate instrument trays with increasing time was 20% at 30 min vs. 43.4% at 120 min). Hence, covering may serves as a barrier to ABCPs and several research support the covering sterile areas to diminish the potential for contamination in the OR [ 12 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown by multiple studies, an important factor of implant and instrument contamination is their exposure to air, which is why the duration of this exposure needs to be as short as possible and laminar airflow ventilation systems should be installed [24][25][26][27]. Additionally, surgical equipment including gloves and gowns play an important role in bacterial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Here, they were able to show that culture positivity directly correlated with the time the trays were openly exposed. Covering the surgical trays led to a significant reduction in contamination rates [25][26][27]. Using a guard in order to shield screws and other implants intraoperatively led to a reduction in bioburden compared to unguarded screws as shown by Agarwal et al in 10 sterile packaged pedicle screws in 2019 [28].…”
Section: Intraoperative Sources Of Implant Contaminationmentioning
confidence: 98%
“…Surgical site infection (SSI) is a dreaded complication after implant surgery [ [1] , [2] , [3] ] often leading to resource demanding treatment and implant replacement [ [4] , [5] , [6] ]. Airborne contamination of the wound, either directly, or indirectly through air-contaminated instruments or implants, has been described as an important risk factor for SSI in orthopedic implant surgery [ [7] , [8] , [9] , [10] ]. Factors such as ventilation system, number of door openings, persons present, size of the operating room (OR) and type of clothing affect airborne microbial contaminants during surgery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%